Eroding the protection against discrimination: The procedural and de-contextualized approach to S.A.S. v France. Issue 2 (June 2019) - Nieminen, Kati
Can human rights law adequately address implicit modes of racism and gender discrimination? This question is discussed in this article through the analysis of the European Court of Human Rights case S.A.S. v. France (2014) concerning the ban on the Islamic full-face veil. The so-called 'headscarf cases' have been thoroughly discussed by many scholars, yet they seem to offer an endless source of different points of view. Departing from the previous discussion on the headscarf and full-face veil cases, which have largely concentrated on the questions of personal autonomy, identity and subjectivity, this article approaches S.A.S. v. France from the point of view of discrimination. It is suggested that the Court's procedural and de-contextualized approach to rights results in eroding the protection against discrimination. Procedural approach refers to the Court's tendency to emphasize procedural aspects of the Convention rights and not to engage sufficiently with substantive analysis. The de-contextual approach to rights on the other hand refers to lack of sensitivity to empirical information concerning the facts of the case at hand. Together the procedural and de-contextual approaches inadvertently erode the protection against discrimination of vulnerable groups, such as Muslim immigrant women.